Assessment of clinical and microbiota responses to fecal microbial transplantation in adult horses with diarrhea - McKinney, Caroline A.; Bedenice, Daniela; Pacheco, Ana P.; Oliveira, Bruno C.M. [UNESP]; Paradis, Mary-Rose; Mazan, Melissa; Widmer, Giovanni (Public Library of Science (PLoS), 2021)
Background and aims Fecal microbial transplantation (FMT) is empirically implemented in horses with colitis to facilitate resolution of diarrhea. The purpose of this study was to assess FMT as a clinical treatment and modulator of fecal microbiota in hospitalized horses with colitis. Methods A total of 22 horses with moderate to severe diarrhea, consistent with a diagnosis of colitis, were enrolled at two referral hospitals (L1: n = 12; L2: n = 10). FMT was performed in all 12 patients on 3 consecutive days at L1, while treatment at L2 consisted of standard care without FMT. Manure was collected once daily for 4 days from the rectum in all colitis horses, prior to FMT for horses at L1, and from each manure sample used for FMT. Fecal samples from 10 clinically healthy control horses housed at L2, and 30 healthy horses located at 5 barns in regional proximity to L1 were also obtained to characterize the regional healthy equine microbiome. All fecal microbiota were analyzed using 16S amplicon sequencing. Results and conclusions As expected, healthy horses at both locations showed a greater α-diversity and lower βdiversity compared to horses with colitis. The fecal microbiome of healthy horses clustered by location, with L1 horses showing a higher prevalence of Kiritimatiellaeota. Improved manure consistency (lower diarrhea score) was associated with a greater α-diversity in horses with colitis at both locations (L1: r = -0.385, P = 0.006; L2: r = -0.479, P = 0.002). Fecal transplant recipients demonstrated a greater overall reduction in diarrhea score (median: 4±3 grades), compared to untreated horses (median: 1.5±3 grades, P = 0.021), with a higher incidence in day-over-day improvement in diarrhea (22/36 (61%) vs. 10/28 (36%) instances, P = 0.011). When comparing microbiota of diseased horses at study conclusion to that of healthy controls, FMT-treated horses showed a lower mean UniFrac distance (0.53±0.27) than untreated horses (0.62±0.26, P<0.001), indicating greater normalization of the microbiome in FMT-treated patients.